Comparative study of the oxygen consumption and anaerobic threshold in a progressive exertion test in professional soccer and indoor soccer athletes - Leal Jr, E. C. P.; Souza, F. de Barros; Magini, M. (Revista Brasileira de Medicina do Esporte, 2006)
Oxygen consumption (VO2) has been very useful for the functional evaluation of athletes. Ergospirometry is a non-invasive procedure used to evaluate the physical performance or the functional ability of an individual, connecting the analysis of the inspired gases with the respiratory variables. This evaluation method is extremely important to sports, since it brings significant contribution in the verification of indices of cardiorespiratory aptitude, which is the case f the maximal oxygen consumption (VO2 max) and the anaerobic threshold (AT). The present study had as objective to compare oxygen consumption and anaerobic threshold in professional soccer and indoor soccer athletes in a progressive test. 31 male individuals voluntarily participated in the test, being: 19 professional soccer athletes and 12 professional indoor soccer athletes. The athletes were submitted to a progressive cardiorespiratory evaluation protocol through the ergospirometric method, and the results were analyzed concerning their statistical difference through the t-Student test (p < 0,05). The average VO2peak indices between the two groups did not present statistically significant difference (p > 0,05); however, there was statistically difference between the two groups concerning the anaerobic threshold (AT) (p < 0,05). Based on the results obtained in our study we concluded that even practicing sports with different characteristics, the athletes from both groups have similar indices of oxygen consumption. Nevertheless, the anaerobic threshold between the two groups did not present the same similarity, suggesting higher predominance of anaerobic metabolism during exercise in the indoor soccer athletes.